Thyroid dysfunction in children and adolescents affected by undernourished and overnourished eating disorders - Calcaterra, Valeria; Magenes, Vittoria Carlotta; Siccardo, Francesca; Hruby, Chiara; Basso, Martina; Conte, Veronica; Maggioni, Giulia; Fabiano, Valentina; Russo, Susanna; Veggiotti, Pierangelo; Zuccotti, Gianvincenzo (Frontiers in Nutrition, 2023)
Eating disorders (ED) are one of the most prevalent chronic disorders in adolescents and young adults, with a significantly increasing prevalence in younger children, particularly in girls. Even if obesity in essence is not framed as an eating disorder and has always been considered a separate pathology, ED and obesity could be considered part of a continuum. It has become evident that one condition can lead to another, such as binge eating disorder (BED) and bulimia nervosa, and that they share the same repercussions in terms of psychosocial, metabolic, and nutritional health. This narrative review aims to investigate the hypothalamic-pituitary-thyroid axis in undernourished and overnourished patients with ED, including obesity, in order to highlight the relationship between weight control and thyroid function and its effects and to consider therapeutic and preventive strategies in children and adolescents. Literature data report that thyroid alterations occur in patients with ED, both underweight and overweight, and represent a continuum of changes depending on the severity and time course of the disease involving the endocrine system. Considering the relevant role thyroid hormones (TH) play not only in energy expenditure (EE) but also in metabolic control and cardiovascular risks related to dysmetabolism and mood regulation, continuous monitoring of thyroid homeostasis in patients with ED is mandatory to prevent severe complications and to start early treatment when necessary.